Obligations and Concerns of an Organization Like the Center for Talented Youth. Issue 1 (September 2015) - Hansen, Elaine Tuttle; Gluck, Stuart; Shelton, Amy L.
Abstract There is another set of entities that needs to be brought into the conversation about the ethical, legal, and social implications of scientific conduct. This widely varied group includes not‐for‐profit educational, academic, public‐service, and philanthropic organizations other than the type mentioned above as well as for‐profit businesses. Despite their major differences, these organizations may all be in a position to make decisions, directly or indirectly, about the conduct of scientific research. And those decisions may have a significant impact on the parties normally involved in thinking and talking about obligations and concerns—the researchers, the subjects, and the general public. Yet there are few if any conceptual frameworks to help organizations address the ethical, legal, and social issues related to conducting scientific research. There are also few resources to help organizations find and develop the expertise required to make responsible decisions or communicate those decisions in ways that could support and advance the ethical conduct of research. In what follows, we try to identify and explore the duties, rights, and interests of one such organization, the Center for Talented Youth at Johns Hopkins University, when asked to play a supporting role in research on the genetics of intelligence. As central agents in this case, we hope to demonstrate why organizations like CTY cannot be neglected in the broader effort to ensure trustworthy research into the genetics of intelligence.